Characterisation of 22 polymorphic microsatellite loci for the Broadbill Swordfish, Xiphias gladius - H. Bradman; P. Grewe; J. Bourjea; D. Muths; B. Appleton (Conservation Genetics Resources, 2011)

Population genetics of invasive common carp Cyprinus carpio L. in coastal drainages in eastern Australia - G. D. Haynes; D. M. Gilligan; P. Grewe; C. Moran; F. W. Nicholas (Journal of Fish Biology, 2010)
The common carp Cyprinus carpio introduced in two drainages in eastern Australia are largely descended from European common carp, and in a third drainage they descend largely from East Asian common carp. The partial genetic differentiation among the species in those drainages is consistent with their origins.

Population genetics and management units of invasive common carp Cyprinus carpio in the Murray–Darling Basin, Australia - G. D. Haynes; D. M. Gilligan; P. Grewe; F. W. Nicholas (Journal of Fish Biology, 2009)
Common carp Cyprinus carpio were introduced into Australia on several occasions and are now the dominant fish in the Murray‐Darling Basin (MDB), the continent's largest river system. In this study, variability at 14 microsatellite loci was examined in C. carpio ( n = 1037) from 34 sites throughout the major rivers in the MDB, from 3 cultured populations, from Prospect Reservoir in the Sydney Basin and from Lake Sorrell in Tasmania. Consistent with previous studies, assignment testing indicated that the Boolara, Yanco and koi strains of C. carpio are present in the MDB. Unique to this study, however, the Prospect strain was widely distributed throughout the MDB. Significant genetic structuring of populations (Fisher's exact test, AMOVA and distribution of the different strains) amongst the MDB sub‐drainages was detected, and was strongly associated with contemporary barriers to dispersal and population history. The distributions of the strains were used to infer the history of introduction and spread of C. carpio in the MDB. Fifteen management units are proposed for control programmes that have high levels of genetic diversity, contain multiple interbreeding strains and show no evidence of founder effects or recent population bottlenecks.

A PL10 vasa-Like Gene in the Kuruma Shrimp, Marsupenaeus japonicus, Expressed During Development and in Adult Gonad - Melony J. Sellars; Russell E. Lyons; Peter M. Grewe; Tony Vuocolo; Lisa Leeton; Greg J. Coman; Bernard M. Degnan; Nigel P. Preston (Marine Biotechnology, 2007)

Genetic stock structure of bigeye tuna in the Indian Ocean using mitochondrial DNA and microsatellites - S. A. Appleyard; R. D. Ward; P. M. Grewe (Journal of Fish Biology, 2002)
Genetic differentiation was minimal and overall non‐significant among five collections of bigeye tuna Thunnus obesus from the Indian Ocean, examined for variation at mitochondrial DNA (mtDNA) and at seven microsatellite loci.

Population structure of yellowfin tuna ( Thunnus albacares ) in the western Pacific Ocean, inferred from microsatellite loci - Appleyard S.; Grewe P.; Innes B.; Ward R. (Marine Biology, 2001)

Allozyme and mitochondrial DNA variation in three species of oreos (Teleostei: Oreosomatidae) from Australasian waters - R. D. Ward; N.G. Elliott; P. M. Grewe; P. R. Last; P. S. Lowry; B. H. Innes; G. K. Yearsley (New Zealand Journal of Marine and Freshwater Research, 1998)
Collections of three species of oreos (smooth oreo, Pseudocyttus maculatus; black oreo, Allocyttus niger; and warty oreo, A. verrucosus ) from Australasian waters were examined for genetic variation. Allozyme heterozygosity was high in each species (25–29 loci: mean heterozygosity per locus per sample ranging from 0.100 to 0.148), but mitochondrial DNA variation was less extensive (10 six‐base restriction enzymes: nucleotide diversity ranging from 0.0012 to 0.0021). Collections of smooth oreos from Western Australia, Tasmania, and New Zealand did not permit the null hypothesis of a single stock to be confidently rejected. Black oreos from Tasmania and New Zealand were provisionally identified as separate stocks. Warty oreos from Tasmania were provisionally identified as separate from a Western Australia/New South Wales stock.

Genetic evidence for depth‐ and spatially separated stocks of the deep‐water spikey oreo in Australasian waters - N. G. Elliott; P. S. Lowry; P. M. Grewe; B. H. Innes; G. K. Yearsley; R. D. Ward (Journal of Fish Biology, 1998)
Samples of Neocyttus rhomboidalis from eight areas off southern Australia and eastern New Zealand were examined to assess the stock structure of the species. No spatial heterogeneity was detected for mitochondrial DNA variation after restriction analysis by two enzymes detecting polymorphic cut sites. Twenty mtDNA haplotypes were recorded, with an overall haplotype diversity of 0·683. Twenty‐eight allozyme loci were examined; the mean heterozygosity per locus was 13·0%. Significant sample heterogeneity was detected at three of twelve polymorphic loci: MPI*, PGM‐1 * and, most strikingly (G ST =0·43), sSOD *. Most of the sSOD * differentiation was associated with depth rather than geographical separation; sSOD * allele frequencies of shallow and deep samples being very different. It is suggested that the correlation between the sSOD * allele frequencies and depth is more likely to reflect natural selection than reproductive isolation. The spatial patterning of the MPI * and PGM‐1 * data suggest there are at least three geographic stocks of N. rhomboidalis in Australasian waters: (1) New Zealand, (2) Western Australia and South Australia, (3) west Tasmania to New South Wales and Lord Howe Rise.

Genetic population structure of southern bluefin tuna ( Thunnus maccoyii ) - P. M. Grewe; N. G. Elliott; B. H. Innes; R. D. Ward (Marine Biology, 1997)